Gestão do conhecimento compartilhado em bibliotecas universitárias : o caso do SIBIUFS - Santos, Sandra Vieira (2020)
Organizations are increasingly aware of the need for new knowledge in companies, knowledge generation involves individuals in a new shared learning format is what is revealed with the knowledge of Knowledge Management, focus of several discussions in Information Science. It is envisioned that organizations can promote Knowledge Management actions through practices and tools capable of stimulating sharing, managing the knowledge produced by members of the organization. In this context the objective of the research: to present an alternative knowledge management and sharing tool favoring the explanation and registration of knowledge that is produced and shared by librarians in SIBIUFS; specific objectives: Identify sharing practices in SIBIUFS; Recognize the technological and non-technological tools used in SIBIUFS; Present an alternative technology tool guide that contributes to knowledge sharing management in SIBIUFS. The methodology is characterized by being descriptive and exploratory, in order to seek theoretical and empirical knowledge on the subject, was used the application of questionnaire, interview, observation, documentary survey, to identify the forms of sharing and tools used to record the knowledge in SIBIUFS. The analysis of the results showed that in SIBIUFS there are consolidated sharing practices among members and supported by management, but technological tools for tacit knowledge management were not listed, which led us to research some tools that could support the shared knowledge management, resulting in a guide to the use of the SIGAA-UFS technology tool.